Amsterdam human capital - Musterd, Sako; Salet, W. G. M. (Amsterdam University Press, 2003)
An interdisciplinary study of the changing urban space of Amsterdam.
Keywords: Regional planning -- Netherlands -- Amsterdam Region.; City planning -- Netherlands -- Amsterdam Region.; Cities and towns -- Research -- Netherlands -- Amsterdam Region.; Humanities.; History.; Society and social sciences.; Sociology and anthropology.; Economics, finance, business and management.; ARCHITECTURE -- Buildings -- Public, Commercial & Industrial.; BUSINESS & ECONOMICS -- Economics -- General.; Cities and towns -- Research; City planning; Regional planning; Netherlands -- Amsterdam Region; Stadsplanning.; Stedelijke ontwikkeling.; Sociaal-economische situatie.; Economics; Economie; Geschiedenis van Amsterdam; History of Amsterdam; Sociologie; Sociology